Sleep quality, daily sleepiness and sleep hygiene at Centro del Adulto Mayor in Lima, Perú - Tello Rodriguez, Tania (2009)
Background: Sleep disorders in the elderly are quite frequent, they significantly affect their quality of life, and sometimes these conditions are poorly recognized by physicians.Objective: To determine sleep quality, the frequency of daily sleepiness and sleep hygiene in elderly at an Elderly Daycare Center in Lima, Peru.Material and methods: 73 elderly persons in an Elderly Daycare Center were interviewed using the previously validated Pittsburgh Sleep Quality Questionnaire, the Epworth Sleepiness Scale and the modified Sleep Hygiene Index.Results: 74% (54 persons) of participants were found to have a poor sleep quality, the component analysis showed that 9,6% of interviewees perceived their sleep quality as poor and very poor (7 persons), 20,2% reported prolonged sleep latency (14 persons), 24,7% reported poor and very poor sleep duration (18 persons), and 52,1% had a less than 85% subjective sleep efficiency (38 persons). Diurnal sleepiness frequency was found in 38,4% of all participants (28 persons). 75,3% reported poor sleep hygiene (55 persons) and 74,1% those with poor sleep quality also had poor sleep hygiene, but this relationship did not reach statistical significance.Conclusion: Persons in this Elderly Daycare Center in Lima, Peru have a high frequency of poor sleep quality, they also commonly report daily sleepiness and a high rate of poor sleep hygiene.